Rwanda Dairy Competitiveness Program II: Efficiency gains in dairy production systems decrease GHG emission intensity - Grewer, Uwe; Nash, Julie; Bockel, Louis; Galford, Gillian L. (2016)
The Rwanda Dairy Competitiveness Program II (RDCP) was estimated to have resulted in a strong decrease in the GHG emissions intensity of milk production, defined as the GHG emissions per unit (liter) of milk produced. Extensive cattle production systems reduced their GHG emission intensity by an estimated - 4.11 tCO2e per 1000 l of milk (-60%), while intensive production systems reduced their intensity by an estimated -1.7 tCO2e/1000 l (- 47%). The decrease in GHG emission intensity is evidence that RDCP made the value chain more efficient and sustainable in climate change mitigation terms.